MODELING HYPERTENSION DISEASE RISK IN INDONESIA USING MULTIVARIATE ADAPTIVE REGRESSION SPLINE AND BINARY LOGISTIC REGRESSION APPROACHES - Chamidah, Nur; Hendrawan, Ardana Tegar; Ardiyanto, Figo Surya; Hammami, Martha Sayyida; Izzah, Nurul; Hariadi, Salsabila Niken (PATTIMURA UNIVERSITY, 2024)
In the pursuit of the Sustainable Development Goals (SDGs), health-related challenges, especially hypertension, remain a significant global issue. The third goal of the SDGs aims to improve the quality of life and well-being of all individuals, but hypertension is a serious problem that can hinder these goals. Often referred to as the